Infrastructure and Network Development to Support the Energy Transition in Indonesia - Antony Antony; Yifan Tang; Marlon Kansil (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Development of the necessary infrastructure and networks to support the energy transition in Indonesia. The energy transition is an important step in facing the challenges of global climate change and the limitations of conventional energy resources. In the context of Indonesia, as a country with a large population and rapid economic growth, it is important to develop adequate energy infrastructure and networks to support the use of renewable energy and better energy efficiency. This study aims to identify the needs and propose the development of infrastructure and networks needed to support energy transition in Indonesia. The specific goal is to design an effective strategy to build infrastructure and networks that are able to accommodate optimal utilization of renewable energy sources. The research method used includes literature study and analysis of relevant qualitative data. This study explores infrastructure and network requirements covering the renewable energy sector, such as renewable power generation, transmission and distribution networks and electric vehicle charging. The results of the study found that energy infrastructure such as wind and solar power had been built but the electricity network was not significant to accommodate the load from this renewable energy. The development of sustainable energy infrastructure and networks must involve proper planning and strategy. This study also discusses the opportunities and challenges that may arise in the development of infrastructure and networks, thereby providing relevant policy recommendations to accelerate Indonesia's sustainable energy transition.